Branje ali branje - Kordigel Aberšek, Metka (Jezik in slovstvo, 1992)
Everyone of us reads sometimes, first in order to get informed, second to learn something, and third because we like to read, because we like literature, briefly, to enjoy. That is why it is not opportune to talk about reading itself (since such a label is not exact enough), but rather about reading in function-thus about pragmatic and literary-aesthetic reading. These represent two diametrally-contrasted reading practices, for the pragmatic one shows reading competence in the speed and versatility in the search for information, the separation of the thing searched for from the context and placing it in the personal thought scheme. This technique has the primary objective in reading rationally with respect to what and how much we want to learn. On the other hand, literature cannot be read slowly enough. We read, because we like to read, and our reading shall be all the more rewarding, the more aesthetic, ethical and cognitive dimensions we are able to perceive. There is, to be sure, no superabundance in literature, for all the poet's expressions uniquely and in a single meaning describle a certain emotion, thought, idea, apparition, vision.
Keywords: Slovene; slovenski jezik; jezikovni pouk; branje